1999
DOI: 10.1159/000047281
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Antagonism and the Heart: Valsartan in Left Ventricular Hypertrophy

Abstract: Left ventricular hypertrophy (LVH) represents an independent risk factor for cardiovascular morbidity and mortality, and normalization of left ventricular mass has become a desirable goal of antihypertensive treatment. In a randomized, double-blind study the angiotensin II (AT1 receptor) antagonist valsartan (Diovan®; 80 mg/160 mg q.d.) was compared with the beta-blocker atenolol (50 mg/100 mg q.d.) over 8 months in predominantly previously untreated patients with essential hypertension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…In another study, left ventricular mass was demonstrated to decrease by 14% with captopril treatment, 30% with enalapril and 12% with lisinopril (20). Another study showed that valsartan reduced cardiac hypertrophy (19). We observed a 19.9% decrease in LVH with three months of valsartan and/or hydrochlorothiazide treatment.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In another study, left ventricular mass was demonstrated to decrease by 14% with captopril treatment, 30% with enalapril and 12% with lisinopril (20). Another study showed that valsartan reduced cardiac hypertrophy (19). We observed a 19.9% decrease in LVH with three months of valsartan and/or hydrochlorothiazide treatment.…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, some antihypertansive agents have no such an effect as expected although they effectively reduce the blood pressure (16). In a study, LVH was shown to be revresed more than 10% in the first eigth weeks, 25% in the first year and more than 40% in the third year (19). In another study, left ventricular mass was demonstrated to decrease by 14% with captopril treatment, 30% with enalapril and 12% with lisinopril (20).…”
Section: Discussionmentioning
confidence: 98%
“…There is clinical evidence suggesting that A II receptor blockers may confer cardioprotective effects superior to those conferred by other classes of antihypertensives, while achieving similar decreases in blood pressure (BP). 2 A more persistent improvement in renal haemodynamics has also been demonstrated for A II receptor blockers in comparison with ACE inhibitors, despite equivalent BP reduction. 3 This could be important in cases of dia- betic nephropathy and chronic renal failure.…”
Section: Introductionmentioning
confidence: 95%
“…5 Valsartan is a selective antagonist of type 1 ATII receptors (AT1) which is effective in reducing arterial pressure 6 and in improving myocardial compliance. 7,8 Some data demonstrates its efficacy in chronic heart failure. 9 Interesting data is emerging about the prevention of and the fight against the atherosclerotic process.…”
Section: Introductionmentioning
confidence: 99%